The awareness of suburban communities on the green technology in Selangor / Norlailin Aimi Mohamed Shoib and Nur Anis Zulaikha Nor Azmi - Mohamed Shoib, Norlailin Aimi; Nor Azmi, Nur Anis Zulaikha (2022)
Green technology is a collection of technologies that help humanity by utilising renewable and nonrenewable energy sources while maintaining ecosystem resilience. Practising green technology will improve the quality of the environment as well as the quality of life of people. Hence, this research was conducted to identify the awareness of suburban communities on green technology in Selangor. The variables that influence the awareness of the community have been analysed in this study, which are government policies & regulations, knowledge level, and attitude towards green technology. This study has been conducted using a non-probability sampling technique by using online questionnaires, and 207 respondents, consisting of a suburban community in Kuala Selangor in Selangor, had answered the distributed questionnaire. The findings of the analysis from this study suggested that the awareness of green technology had a significant relationship with all the variables studied. However, the knowledge level on green technology has been found to be the strongest predictor that influences the awareness of suburban communities on green technology.